PEMANFAATAN MODEL GINJAL DAN LKS BERJENJANG DALAM PEMBELAJARAN SISTEM EKSKRESI MANUSIA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS IX1 SMP NEGERI 1 WAWO - Eddy Ilhamsyah (Lembaga Penelitian dan Pendidikan Mandala, 2017)
This teaching innovation research aims at knowing whether or not the use of Kidney Model and Step-by-step Students’ Worksheet can increase learning motivation and learning outcomes of Grade IX1 students of SMPN 1 Wawo in school year 2015/2016. Data collection were conducted by using progressive test instruments, performance test instrument, the observation forms of students’ learning observation, and questionnaire toward the use of kidney model and step-by-step students’ worksheet in teaching Human Excretion System. The quantitative data analysis on the result of progressive test was conducted by using the analysis of progressive test result form, while the qualitative data analysis on observation technique was by scoring on each aspect observed or on their answer alternatives. Based on the analysis of progressive test result in the last two years (previous condition), the number of students acquiring score above the passing grade was 13 (47.27%) on average, and those whose score was below the passing grade was 14.5 students (52.72%) with the average score was 61.18. However, the result of students’ progressive test after the teaching innovation implemented was significantly increased in which the students who got above the passing grade were 19 (86.39%) in total, and those who failed were only 3 (13.63%) with the average score was 75.45. It indicates that the students’ scores were higher than the passing grade (KKM) demanded on Basic Competence of Human Excretion System, i.e. 75.00 (85%) on average. Furthermore, the data analysis on students’ motivation in learning Human Excretion System using the kidney model and step-by-step students’ worksheet shows that from 22 students, the average score on the students’ attention on the experiment (teaching-learning activity) was 3.70 or 92.5 meaning outstanding, questioning and giving opinion 3.09 or 77.25 (good), and the participation in group-work 3.40 or 85 (outstanding). Thus, the average score on students’ learning motivation was 3.39 or 84.75 meaning outstanding. Based on the data analysis above, it is concluded that the use of Kidney Model and Step-by-Step Students’ Worksheets in teaching Human Excretion System can increase motivation and learning outcomes of Grade IX1 Students of SMPN 1 Wawo in School Year 2015/2016